Does Parental Co-creation Impacts Perceived Value? A Mixed-method Study in Indian Elementary Educational Innovations. Issue 1 (March 2020) - Dasgupta, Meeta; Prashar, Anupama
Research on building innovative practices for enhancing the educational effectiveness has gained momentum. Schools as business units play a critical role in building effectiveness. Empirical investigation on the role of parents, the primary customers taking decisions with respect to availing school services for their children, as co-creators in conceptualizing and executing educational innovations is thin. To bridge this research gap, a mixed methods study was conducted on a sample of elementary schools in India. The study also investigated the impact of parents' involvement on their perceived value and satisfaction. The results suggested that schools are undertaking various innovative initiatives in which parents play a primary role in execution both at home and in the school. It was found that parents' perception of value for innovative practices introduced by the schools is high, irrespective of their low involvement in the conceptualization stage. The findings also indicated that parental involvement in the execution stage of the initiatives impacts their perceived value more than at the conceptualization stage.